Energy Usage, Internet Usage and Human Development in Selected Western African Countries - Ejemeyovwi, Jeremiah; Adiat, Queen; Ekong, Edikan (International Journal of Energy Economics and Policy, 2019)
The examination of energy usage and ICT usage in terms of their role in the improvement of human development was the study's objective. A panel analysis is carried out on World Bank data (2000-2014) from selected Western African countries, with notable energy usage within the region. The study utilizes generalized least squares (GLS), the fixed effect (FEM) and the random effect (REM) econometric estimation techniques to determine the degree of relationship and impact existing between the variables of interest. The results indicate that internet usage and energy usage affect human development in the selected West African countries. The policy implication from the findings posit that it is expedient that the government and private sector, exert financial and non-financial contributions to ensure that energy and ICT facilities are readily available for use. This would improve the level of the two major human development components (health and education). Keywords: Energy usage, ICT usage, Human development, Western Africa. JEL Classification: Q4 DOI: https://doi.org/10.32479/ijeep.7611